Understanding the relationships between postcards as image makers and postcard induced emotions with a desire to travel / Nurul Aziah Ahmad - Ahmad, Nurul Aziah (2013)
Nowadays, due to the growing advance of electronic communication such as e-cards, video postcards and the era of email, understanding of postcards’ potential power in generating interest toward a destination is important. However there is lack of research on postcards within the context of destination image representation. Thus, the purpose of research is to understand the relationships between postcards as image makers and postcards-induced emotions towards the desire to travel to help the destination marketer in determining the effectiveness of postcards as marketing and promotional tools towards the destination. This research was conducted in SkyPos Langkawi and Selangor with total of 80 respondents. Whereby, due to the unavailability in estimating the targeted respondents, nonprobability and purposive sampling design were used. Next, the findings reported that postcards as image makers had a significant relationship towards desire to travel as well as postcard-induced emotions which was significantly impact towards desire to travel. Apart from that, the result also confirmed that destination image act as a moderator for all the relationships. Thus, three objectives of this research were successfully achieved and answered. Lastly, the research also put forward with some implications pertain to the development of theoretical and practical understanding about the relationships of postcards as image makers and postcards-induced emotions in generating a desire to travel.